Zoe the skating fairy - Meadows, Daisy (New York : Scholastic Inc., 2010)
While everyone in Fairyland is getting ready for the Fairy Olympics, Jack Frost's goblins steal the Sports Fairies' magic objects, and Rachel and Kristy are determined to roll away with Zoe's magic shoelace
Originally published with series title The sporty fairies: London : Orchard Books, 2008
2
006-009
Keywords: Walker, Rachel (Fictitious character) -- Juvenile fiction; Tate, Kirsty (Fictitious character) -- Juvenile fiction; Fairies -- Juvenile fiction; In-line skating -- Juvenile fiction; Olympics -- Juvenile fiction; Magic -- Juvenile fiction; Jack Frost (Legendary character) -- Juvenile fiction; Goblins -- Juvenile fiction; Fantasy fiction -- Juvenile fiction; Sports stories -- Juvenile fiction; Walker, Rachel (Fictitious character) -- Fiction; Tate, Kirsty (Fictitious character) -- Fiction; Fairies -- Fiction; In-line skating -- Fiction; Olympics -- Fiction; Sports -- Fiction; Magic -- Fiction; Jack Frost -- Fiction; Goblins -- Fiction